Cu adsorption behaviours onto chelating resins from glycine-cyanide solutions: Isotherms, kinetics and regeneration studies - Deng, Zixian; Oraby, Elsayed; Eksteen, Jacques (ELSEVIER, 2020)
© 2019 Elsevier B.V.